Development of DOB Social Isolation Scale: Validity and Reliability - Gülgün, Durat; Kevser, Ilcioglu; Yasemin, Hamlaci Baskaya (Bangladesh Journal of Medical Science, 2023)
Objectives: The situation in which an individual disconnects their communication from their environment and avoids collective activities is called “social isolation”.Based on the literature reviewed, the measurement tools’ validity and reliability studies that were previously made were not sufficient in measuring the concept of social isolation. The study was conducted to develop a scale to evaluate social isolation. Methods: This methodologically was conducted with 584 university students between February and June 2019. The draft of the Social Isolation Scale was reviewed in the literature, and an item pool of 31 items in 5-point Likert type was created. Suggestions from 11 experts were evaluated. Finally, a scale with 28 items was prepared, and the items were corrected in terms of language and expression in line with expert opinion. The data were collected via a questionnaire prepared by the researchers. Results: The mean age of the students was detected as 20.45 ± 2.33. Ten items were removed from the scale because their factor load was under 0.500. It was determined that the scale consists of eighteen items and the sole factor. The internal consistency coefficient (Cronbach’s alpha) of the scale was calculated as 0.912. Conclusion: This study demonstrates that the “DOB Social Isolation Scale” is a valid and reliable measurement instrument. Developed to measure social isolation, the DOB Social Isolation Scale is an adaptable scale to different cultures. The scale provides an advantage for healthcare professionals in determining social isolation. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 403-409